Hubungan Oral Hygiene Habits dengan Early Childhood Caries (ECC) pada Balita Di Kota Padang - Zhafirah Muharani Nasution; Reni Nofika; Susi Susi (Faculty of Dentistry Universitas Andalas, 2020)
Dental caries is a disease of hard tissue of the tooth due to bacterial activities that cause loss mineral structure of the tooth. Dental caries that occur in deciduous teeth on children under 71 months is called Early Childhood Caries (ECC). Dental caries is still one of the most common dental and oral health problem experienced by children in the world. Some surveys in Cambodia and Indonesia show that a high prevalence and severity of ECC which was 90% in children aged 3-5 years. Oral hygiene habits were identified as one of the risk factors of caries. Some studies suggest that there is a strong relationship between the behavior of maintaining oral hygiene and the prevalence of dental caries. The purpose of this study is to determine the relationship between oral hygiene habits and early childhood caries on toddler in Padang. This study used cross sectional design. The samples of this study was 107 childrens aged 3-5 years in Padang. The location was selected through stratified random sampling technique and samples was selected through consecutive sampling techniques. Data was collected in Gunung Pangilun village and Piai Tanah Sirah village. Data was collected using a questionaires and intraoral examination. Data was analyzed by Chi-Square with p<0,05. The result of this study that there was a significant relationship between oral hygiene habits and ECC on toddler in Padang (p=0,008). The conclusion of this study was that oral hygiene habits is associated with early childhood caries on toddler in Padang.